Thermal expansion of quaternary nitride coatings. (6th March 2018) - Tasnádi, Ferenc; Wang, Fei; Odén, Magnus; Abrikosov, Igor A
Abstract: The thermal expansion coefficient of technologically relevant multicomponent cubic nitride alloys are predicted using the Debye model with ab initio elastic constants calculated at 0 K and an isotropic approximation for the Grüneisen parameter. Our method is benchmarked against measured thermal expansion of TiN and Ti(1− x ) Al x N as well as against results of molecular dynamics simulations. We show that the thermal expansion coefficients of Ti(1− x − y ) X y Al x N (X  =  Zr, Hf, Nb, V, Ta) solid solutions monotonously increase with the amount of alloying element X at all temperatures except for Zr and Hf, for which they instead decrease for y ≳ 0.5 .